Sound-absorbing urethane foam

A specially formulated urethane foam with controlled polyol components and catalysts achieves high sound absorption in the 1000Hz to 3150Hz range, addressing the limitations of existing materials by enhancing sound insulation and shock absorption in vehicles.

JP7625399B2Active Publication Date: 2025-02-03TOKYO QUALITY ONE CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020183798
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-27
Filing Date
2020-11-02
Publication Date
2025-02-03
Estimated Expiration
2040-11-02

AI Technical Summary

Technical Problem

Existing shock absorbing materials in vehicles, such as rigid polyurethane foam and thermoplastic resin beads, lack effective sound absorbing performance, especially in a wide frequency band, and are difficult to make thin while maintaining sound insulation.

Method used

A sound-absorbing urethane foam with a diameter of 29 mm and thickness of 10 mm exhibits a vertical incident sound absorption rate of 40% or more in the frequency range of 1000Hz to 3150Hz, achieved by a specific formulation of polyol components with controlled molecular weights and ethylene oxide content, catalysts, and isocyanate index, forming a porous elastic structure with balanced breathability.

Benefits of technology

The urethane foam provides excellent sound absorption in low-frequency bands, reducing noise perception for vehicle occupants, while maintaining practical shock absorption and allowing for thin profiles to reduce vehicle weight and increase interior space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625399000003
    Figure 0007625399000003
  • Figure 0007625399000004
    Figure 0007625399000004
  • Figure 0007625399000005
    Figure 0007625399000005
Patent Text Reader

Abstract

To provide sound absorption polyurethane foam excellent in sound absorption performance.SOLUTION: There is provided sound absorption polyurethane foam in an embodiment. In the sound absorption polyurethane foam, a diameter is 29 mm, and a vertical incidence sound absorption coefficient at a thickness of 10 mm is 40% or higher in the whole area of a frequency range of 1,000 Hz-3,150 Hz.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sound-absorbing urethane foam. [Background technology]

[0002] Conventionally, shock absorbing materials have been installed inside the doors, around the ceiling, and inside the pillars of automobiles to protect passengers against external shocks while in the automobile. Known shock absorbing materials include, for example, rigid polyurethane foam and foamed thermoplastic resin beads.

[0003] In addition, in today's automobiles, there is a demand for controlling noises such as engine noise and tire running noise, and for improving the quietness inside the vehicle. However, the above-mentioned rigid polyurethane foam and foamed thermoplastic resin beads generally have a closed cell structure, and therefore have a problem of poor sound absorption performance. Although a technique for imparting an open cell structure to the rigid polyurethane foam and foamed thermoplastic resin beads is known, it is difficult to impart excellent sound absorption performance in a wide frequency range when the wall thickness is thin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-047338 A [Patent Document 2] JP 2005-272806 A [Patent Document 3] Patent No. 4461453 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above circumstances, and has an object to provide a sound-absorbing urethane foam having excellent sound-absorbing performance. [Means for solving the problem]

[0006] According to one aspect of the present invention, there is provided a sound-absorbing urethane foam having a diameter of 29 mm and a thickness of 10 mm, with a normal incidence sound absorption coefficient of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz. The sound-absorbing urethane foam is obtained by foaming in a reaction system containing a polyol, a polyisocyanate, a blowing agent, a catalyst, and an additive. The polyol contains polyol A having a weight-average molecular weight in the range of 2000 to 12000 and an ethylene oxide content of 50% by weight or more, and polyol B having a weight-average molecular weight in the range of 4000 to 12000 and an ethylene oxide content in the range of 5% by weight or more and less than 50% by weight. The weight of polyol A in the weight of the polyol is in the range of 35% by weight to 80% by weight. The catalyst contains diethanolamine. The sound-absorbing urethane foam has an isocyanate index in the range of 130 to 250. Effect of the Invention

[0007] According to the present invention, it is possible to provide a sound-absorbing urethane foam having excellent sound-absorbing performance. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a plan view showing an example of a sound-absorbing urethane foam. [Diagram 2] 2 is a cross-sectional view showing a cross section of the sound-absorbing urethane foam shown in FIG. 1 taken along line II-II. [Diagram 3] 3 is a cross-sectional view showing a cross section of the sound-absorbing urethane foam shown in FIG. 1 taken along line III-III. [Figure 4] FIG. 2 is a schematic diagram showing how sound waves propagate through a porous elastic material. [Diagram 5] FIG. 2 is a schematic diagram showing how an incident wave entering the skeleton of a porous elastic material is attenuated. [Figure 6] 4 is a sound absorption coefficient graph showing the measurement results of the normal incidence sound absorption coefficient of the sound-absorbing urethane foam according to the embodiment. [Figure 7] 4 is a sound absorption coefficient graph showing the measurement results of the normal incidence sound absorption coefficient of the sound-absorbing urethane foam according to the embodiment. [Figure 8] 4 is a sound absorption coefficient graph showing the measurement results of the normal incidence sound absorption coefficient of the sound-absorbing urethane foam according to the embodiment. [Figure 9] 4 is a sound absorption coefficient graph showing the measurement results of the normal incidence sound absorption coefficient of the sound-absorbing urethane foam according to the embodiment. [Figure 10] 4 is a sound absorption coefficient graph showing the measurement results of the normal incidence sound absorption coefficient of the sound-absorbing urethane foam according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A lower leg impact absorbing material is installed on the floor of a general automobile. Conventionally, the main materials for the lower leg impact absorbing material are expanded polypropylene and expanded polyethylene, which have excellent impact absorbing performance, but rigid urethane foam, which has not only impact absorbing performance but also sound absorbing performance, is also used. Rigid urethane foam is characterized by being lighter and stronger than, for example, expanded polypropylene.

[0010] The noise perceived by the passengers inside the vehicle has a high sound pressure level in the low frequency band. Therefore, shock absorbing materials installed in automobiles are required to have not only a certain shock absorbing performance (buckling property) but also, for example, excellent sound absorbing performance in the low frequency band. Recently, there has been an increasing demand to reduce the thickness of shock absorbing materials in order to realize a large interior space and to reduce the vehicle weight. In other words, there is a demand to realize excellent sound absorbing performance and practical shock absorbing performance with a shock absorbing material that is as thin as possible.

[0011] The sound-absorbing urethane foam according to the embodiment has a normal incidence sound absorption coefficient of 40% or more in the entire frequency range of 1000Hz to 3150Hz when the diameter is 29mm and the thickness is 10mm. For example, a normal incidence sound absorption coefficient measurement performed on a block of 29mm diameter and 10mm thickness shows that the normal incidence sound absorption coefficient is 40% or more in the entire frequency range of 1000Hz to 3150Hz. This block can be at least a part of the sound-absorbing urethane foam according to the embodiment. That is, the block is the sound-absorbing urethane foam itself, or a urethane foam cut into a cylindrical shape having the above dimensions from a sound-absorbing urethane foam having a size that allows cutting out a cylindrical shape of 10mm thickness and 29mm diameter. In this specification, the "normal incidence sound absorption coefficient" may be abbreviated to "sound absorption coefficient".

[0012] A sound-absorbing urethane foam having a thickness of 10 mm and a normal incidence sound absorption coefficient of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz can be said to have excellent sound-absorbing performance. It is preferable that the sound-absorbing urethane foam has a designed surface. The designed surface refers to the surface that was in contact with the upper mold of the metal mold during molding, for example, when the urethane foam is obtained by molding. The designed surface is also called the skin or skin surface. Whether or not the sound-absorbing urethane foam has a designed surface can be determined by observing the surface and / or cross section of the sound-absorbing urethane foam with a scanning electron microscope (SEM).

[0013] <Method for measuring normal incidence sound absorption coefficient> First, a cylindrical urethane foam block with a diameter of 29 mm (29φ) and a thickness of 10 mm is prepared as the object for measuring the sound absorption coefficient. The block is produced by molding using a die that gives the block a thickness of 10 mm. The block can be prepared using a punching machine equipped with a 29φ punching die. Five of these blocks are prepared to calculate the average value of the sound absorption coefficient measurement results.

[0014] The sound absorption coefficient measurement device used is the Acoustic Duct / Transfer Function Method Normal Incidence Acoustic Measurement System Model 9301 manufactured by Rion Co., Ltd., or a device with equivalent functions. The normal incidence acoustic measurement system can measure the sound absorption coefficient, acoustic impedance related items, and transmission loss of the material by irradiating sound perpendicularly onto a sound absorbing or insulating material inside an acoustic tube (acoustic duct) and capturing the reflected or transmitted sound. Start the normal incidence acoustic measurement system, calibrate the microphone, and complete preparations for the sound absorption coefficient measurement.

[0015] The sound absorption coefficient is measured by setting the block at a specified position inside the duct so that sound is incident in a direction parallel to the thickness direction of the block. The sound absorption coefficient measurement is performed in accordance with JIS A 1405:1994. If the block has a decorative surface, the block is set so that sound is incident on this decorative surface.

[0016] Then, the normal incidence sound absorption coefficient is measured for frequencies of 500Hz, 630Hz, 800Hz, 1000Hz, 1250Hz, 1600Hz, 2000Hz, 2500Hz, 3150Hz, 4000Hz, 5000Hz, and 6300Hz. This measurement is performed for each of the five blocks, and the normal incidence sound absorption coefficient at each frequency is calculated, so that the normal incidence sound absorption coefficient at each frequency can be determined. Based on the measurement results, a line graph can be created in which the horizontal axis indicates frequency (Hz) and the vertical axis indicates sound absorption coefficient (%). In this specification, this line graph is referred to as a "sound absorption coefficient graph." As will be described later in connection with Figs. 6 to 8, the normal incidence sound absorption coefficient at each frequency can be determined. 10 The sound absorption coefficient graph is a logarithmic graph.

[0017] When the sound absorption coefficient of the object being measured is 40% or more at all frequencies of 1000Hz, 1250Hz, 1600Hz, 2000Hz, 2500Hz, and 3150Hz, it can be considered that the normal incidence sound absorption coefficient is 40% or more over the entire frequency range of 1000Hz to 3150Hz.

[0018] As a result of normal incidence sound absorption measurement, the sound-absorbing urethane foam has a normal incidence sound absorption rate of preferably 45% or more, and more preferably 50% or more, in the entire frequency range of 1000Hz to 3150Hz. When the sound-absorbing urethane foam is used as a lower limb shock absorbing material for an automobile or the like, the higher the sound absorption rate in the entire frequency range of 1000Hz to 3150Hz, the less likely the passengers of the automobile or the like are to perceive low frequency band noise. Therefore, the passengers can spend their time comfortably while riding in the automobile. The low frequency band refers to, for example, a frequency range of 1000Hz to 3150Hz.

[0019] From the viewpoint of effectively absorbing noise in the low frequency band, it is preferable that the sound-absorbing urethane foam has a peak sound absorption coefficient at a frequency of 1000Hz to 2000Hz in the sound absorption coefficient graph obtained as a result of normal incidence sound absorption coefficient measurement. In this case, the sound absorption coefficient at, for example, 500Hz to 2000Hz is excellent. For example, as shown in the sound absorption coefficient graph in FIG. 6, Example 8 as an embodiment shows the most excellent sound absorption coefficient at a frequency of 1600Hz. In other words, Example 8 has a peak sound absorption coefficient at a frequency of 1600Hz. Therefore, the sound-absorbing urethane foam according to Example 8 can effectively absorb noise in the frequency band of 500Hz to 2000Hz.

[0020] The shape and dimensions of the sound-absorbing urethane foam are not particularly limited. The sound-absorbing urethane foam has a portion having a thickness of, for example, 15 mm or less. The normal incidence sound absorption coefficient is measured, for example, on a block extracted from a portion having a thickness of 15 mm or less. Even in a portion having a thickness of 15 mm or less, the sound-absorbing urethane foam preferably has a diameter of 29 mm and a normal incidence sound absorption coefficient at a thickness of 10 mm of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz. The block has, for example, a cylindrical shape having a diameter of 29 mm and a thickness of 10 mm.

[0021] In one example, the sound-absorbing urethane foam has a portion with a thickness of 10 mm or more, but it does not have to have a portion with a thickness of 10 mm or more. In such a case, when preparing a block for measuring the normal incidence sound absorption coefficient of the sound-absorbing urethane foam, a urethane foam with a thickness of 10 mm or more is manufactured with the same composition as the sound-absorbing urethane foam, and a block with a diameter of 29 mm and a thickness of 10 mm is prepared from the manufactured urethane foam, and the normal incidence sound absorption coefficient measurement is performed on this block.

[0022] FIG. 4 shows a model diagram of sound propagation in a porous elastic material such as urethane foam. The sound-absorbing urethane foam according to the embodiment has, for example, the porous elastic structure shown in FIG. 4. The porous elastic body 100 is made of a skeleton 101 having a three-dimensional lattice structure. The skeleton 101 includes an isocyanurate structure including a urea bond and a urethane bond. The isocyanurate structure is a cyclic structure formed by a trimerization reaction of an isocyanate. The porous elastic body 100 includes voids 102 between the lattices formed by the skeleton 101. The voids 102 may be openings. The sizes of the multiple lattices formed by the skeleton 101 are not uniform.

[0023] A sound wave SW is incident on the porous elastic body 100. The vibrations transmitted by the sound wave SW generate an air-propagating wave 103 passing through the voids 102 and a solid-propagating wave 104 propagating through the skeleton 101. The air-propagating wave 103 and the solid-propagating wave 104 interact with each other while they are propagating, and each of the propagating waves is attenuated (sound absorption). A part of the incident wave that is incident on the skeleton 101 as the solid-propagating wave 104 is attenuated by being converted into thermal energy as shown in FIG. 5. As shown in FIG. 5, a part of the incident wave I that is incident on the skeleton 101 collides with the skeleton 101 and is reflected as a reflected wave R. Another part of the incident wave I that is incident on the skeleton 101 is emitted from the skeleton 101 to the outside of the skeleton 101 as a transmitted wave T after propagating through the skeleton 101. The wave that is incident on the skeleton 101 can be converted into thermal energy r while propagating through the skeleton 101.

[0024] The sound absorption rate of sound-absorbing urethane foam varies depending on how the skeleton in the sound-absorbing urethane foam is constructed. From the viewpoint of sound absorption rate, it is not preferable if the ratio of the cyclic structure in the skeleton 101 is too small, and it is also not preferable if it is too large. In order to improve the sound absorption performance of sound-absorbing urethane foam, it is effective to mix not only closed cell structure but also open cell structure. When manufacturing sound-absorbing urethane foam by foaming, if the equivalent weight of polyol is increased, it tends to be difficult to form a membrane. In other words, there is a tendency for more open cell structures to be formed. In that case, the portion existing as a lattice structure is relatively reduced, so that sound waves are difficult to propagate through the voids 102 and are difficult to convert into thermal energy, which may result in a decrease in sound absorption performance.

[0025] Focusing on the breathability of sound-absorbing urethane foam, for example, reducing the breathability of the foam promotes the conversion of sound waves into thermal energy, which tends to improve sound absorption performance. However, if the breathability is reduced too much, the amount of sound waves emitted as reflected waves increases, which tends to deteriorate the sound absorption performance.

[0026] For example, the air permeability of a 10mm thick sound-absorbing urethane foam is 0.5cc / cm 2 / sec or more and 40 or less cc / cm 2 By keeping the air permeability within this range, a good sound absorption coefficient can be obtained in the low frequency range. The air permeability of a sound-absorbing urethane foam with a thickness of 10 mm is 10cc / cm 2 / sec or more and 30 or less cc / cm 2 The breathability can be measured in accordance with JIS K6400 7 B method:2012.

[0027] The raw materials and the composition for obtaining the sound-absorbing urethane foam according to the embodiment will be described. The sound-absorbing urethane foam is obtained by foaming in a reaction system containing, for example, polyol, polyisocyanate, a foaming agent, a catalyst, and additives. From the viewpoint of easily controlling the structure of the bubbles, molding is preferred as a manufacturing method.

[0028] When a polyurethane foam is produced by molding, a liquid obtained by mixing and stirring a polyol component and a polyisocyanate component is poured into a mold. When these components are cured, a foaming reaction and a resinification reaction proceed simultaneously. Therefore, when a polyurethane foam having a thin wall portion, for example a portion having a thickness of 10 mm or less, is molded, it is desirable that the molding proceeds appropriately even in a part of the mold corresponding to the portion. In other words, it is desirable that the thin wall portion of the obtained polyurethane foam does not have defects such as skin peeling, underfill, air pockets, and cracks. A sound-absorbing polyurethane foam that has few defects and can be produced in a desired shape has excellent moldability. Moldability varies depending on various factors, but it is desirable that the sound-absorbing polyurethane foam according to the embodiment has excellent moldability in the thin wall portion.

[0029] In order to obtain a sound-absorbing urethane foam having a normal incidence sound absorption rate of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz as a result of normal incidence sound absorption rate measurement, it is preferable that the polyol component (polyol) as a raw material contains the following polyol B. Polyol B has a weight average molecular weight in the range of 4000 to 12000 and an ethylene oxide content of 5% by weight or more and less than 50% by weight. Polyol B is, for example, polypropylene glycol having a hydroxyl group at the end. When polyol B having a weight average molecular weight of 4000 or more is used, crosslinking points during the reaction can be reduced, so that a urethane foam with low breathability can be obtained. As described above, a urethane foam with low breathability has excellent sound absorbing performance.

[0030] In addition, a complex shape includes, for example, a shape that includes a portion with a thickness of 15 mm or less. When performing the normal incidence sound absorption coefficient measurement described above, it is desirable to extract the block to be measured so that it includes a portion with a thickness of 15 mm or less. This is because a urethane foam with excellent sound absorption performance in such a thin portion can be estimated to be a sound-absorbing urethane foam with excellent sound absorption performance overall.

[0031] If the weight average molecular weight of polyol B exceeds 12,000, the viscosity of polyol B is too high, so that it may be impossible to mold a sound-absorbing urethane foam. Alternatively, since the molecular chain is long, the crosslink density after molding is low and the foam tends to be too soft, so that it may be impossible to obtain a proper foam. At the time of filing this application, polyols with a weight average molecular weight of more than 12,000 are not commercially available and are difficult to obtain.

[0032] The weight average molecular weight of polyol B is preferably within the range of 5,000 to 8,000, and more preferably within the range of 6,500 to 7,500.

[0033] Since the ethylene oxide content of polyol B is less than 50% by weight, it has a higher retention of bubbles generated during the foaming process than polyol A described later. In addition, when the ethylene oxide content is less than 50% by weight, a film tends to be easily formed in the sound-absorbing urethane foam obtained, so that the breathability is low and the sound absorption rate in the low frequency range tends to be excellent. This is considered to be because incident waves in the low frequency range are input to the sound-absorbing urethane foam with low breathability, and the incident waves are converted into thermal energy and absorbed inside the sound-absorbing urethane foam. By using polyol B, it becomes easier to obtain a sound-absorbing urethane foam that is excellent not only in sound absorption performance but also in moldability. The ethylene oxide content of polyol B is preferably in the range of 5% by weight to 40% by weight, more preferably in the range of 5% by weight to 30% by weight.

[0034] Polyol B preferably has a terminal ethylene oxide cap structure.

[0035] The hydroxyl value of polyol B is preferably 14 mgKOH / g or more and 56 mgKOH / g or less.

[0036] The polyol component (polyol) preferably further contains the following polyol A. The polyol A has a weight average molecular weight in the range of 2000 to 12000 and an ethylene oxide content of 50% by weight or more. The polyol A is, for example, a polyether polyol. The polyol A has a higher polarity than the polyol B. Therefore, by using the polyol A in combination with the polyol B, a polyurethane foam having a more interconnected cell structure can be obtained compared to the use of only the polyol B. That is, a polyurethane foam having a moderately interconnected cell structure can be obtained, and such a polyurethane foam has excellent sound absorbing performance. In addition, the polyol A also has a relatively high weight average molecular weight, which contributes to obtaining a sound absorbing urethane foam having excellent moldability.

[0037] The weight average molecular weight of polyol A is preferably within the range of 6,500 to 10,000, and more preferably within the range of 7,000 to 9,000.

[0038] The hydroxyl value of the polyol A is preferably 18 mgKOH / g or more and 52 mgKOH / g or less.

[0039] The polyol component may contain other polyols different from polyol A and polyol B. Examples of other polyols include polyether polyols having a weight average molecular weight of 1000 or more and less than 4000, an ethylene oxide content of less than 5%, and a hydroxyl value of 40 mgKOH / g or more. By blending a polyether polyol having a weight average molecular weight of less than 4000 as the other polyol, there is an effect of easily imparting impact absorbing performance (buckling property).

[0040] In one example, the blending ratios of polyol A, polyol B and other polyols in the polyol component (polyol) can be 35% to 80% by weight, 5% to 40% by weight and 5% to 30% by weight, respectively. However, they are blended so that the total of these amounts to 100% by weight. The blending ratios can be appropriately adjusted as long as the normal incident sound absorption coefficient of the obtained sound-absorbing urethane foam is 40% or more over the entire frequency range of 1000Hz to 3150Hz.

[0041] The weight ratio of polyol B to the weight of the polyol component (polyol) may be within the range of 5% by weight to 40% by weight. If the weight ratio of polyol B to the weight of the polyol component is too low, the sound-absorbing urethane foam will have high air permeability, and the sound absorption coefficient in the frequency range of 1000 Hz to 3150 Hz may decrease. On the other hand, if the weight ratio of polyol B to the weight of the polyol component is too high, the air permeability may decrease, and the sound absorption coefficient in the frequency range of 1000 Hz to 3150 Hz may decrease. The weight ratio of polyol B to the weight of the polyol component (polyol) is preferably within the range of 5% by weight to 30% by weight.

[0042] The weight ratio of polyol B to the weight of the polyol component may be within a range of 5% by weight to 20% by weight, 5% by weight to 15% by weight, or 10% by weight to 20% by weight.

[0043] The weight ratio of polyol A to the weight of the polyol component is preferably within the range of 50% by weight to 75% by weight. The weight ratio of polyol A to the weight of the polyol component may be within the range of 50% by weight to 80% by weight, 55% by weight to 75% by weight, 60% by weight to 75% by weight, or 65% by weight to 75% by weight.

[0044] The proportion of the weight of the other polyol in the weight of the polyol component may be within a range of 10% by weight to 30% by weight, or may be within a range of 15% by weight to 25% by weight.

[0045] The blending ratios of polyol A, polyol B and other polyols in the polyol component can be determined by appropriately combining the above-mentioned numerical ranges. For example, the weight ratio of polyol A can be set within the range of 55% by weight to 75% by weight, the weight ratio of polyol B can be set within the range of 5% by weight to 15% by weight, and the weight ratio of other polyols can be set within the range of 15% by weight to 25% by weight.

[0046] As the polyisocyanate, it is preferable to use diphenylmethane diisocyanate (MDI). Diphenylmethane diisocyanate may be monomeric MDI, polymeric MDI, or a mixture thereof. Polyisocyanate may contain only one type of MDI, or may contain two or more types. MDI has good curing properties compared to toluene diisocyanate (TDI), and is therefore excellent in terms of molding.

[0047] The isocyanate index during the production of the sound-absorbing urethane foam is, for example, in the range of 100 to 250, and preferably in the range of 130 to 180. However, as long as the normal incidence sound absorption rate of the obtained sound-absorbing urethane foam is 40% or more over the entire frequency range of 1000 Hz to 3150 Hz, there is no limitation on the isocyanate index during the production of the urethane foam. If the isocyanate index is too low, the molding (molding) of the urethane foam itself may be difficult, and it may not be possible to remove it from the mold. If the isocyanate index is too high, only the surface (skin) is present, and there are excessively many voids or cavities inside. In other words, since the foam has a coarse mesh structure, when it is produced by molding, it is easily broken when demolded.

[0048] As the catalyst, a resinification catalyst, an isocyanurate catalyst (trimerization catalyst), a surface modification catalyst, a foaming catalyst, etc. can be used. As each catalyst, a known catalyst used for the intended purpose can be used.

[0049] The resinification catalyst is used, for example, in an amount of 1 to 3 parts by weight relative to the weight of the polyol component. The isocyanuration catalyst is used, for example, in an amount of 2 to 5 parts by weight relative to the weight of the polyol component. The surface modification catalyst can be used, for example, in an amount of 0.5 to 5 parts by weight relative to the weight of the polyol component, and is preferably used in an amount of 1 to 3 parts by weight. The foaming catalyst is used, for example, in an amount of 0.1 to 1 part by weight relative to the weight of the polyol component.

[0050] As the surface modification catalyst, diethanolamine (DEA) is preferably used. DEA has OH groups at both ends. These OH groups crosslink with the NCO groups of the isocyanate, which increases the strength of the skeleton of the resulting polyurethane foam, improving or stabilizing moldability and suppressing skin peeling. As a result, molding of complex shapes is possible. For example, even if the shape has a thin wall portion, cracking during demolding can be suppressed. In other words, polyurethane foam containing DEA can achieve excellent moldability even in molding of complex shapes.

[0051] As other additives, for example, a foam stabilizer and / or a plasticizer can be added. The foam stabilizer and the plasticizer can improve the moldability of the polyurethane foam. The other additives are used in an amount of, for example, 5 to 30 parts by weight based on the weight of the polyol component.

[0052] The blowing agent may be any known one used in the manufacture of general polyurethane foams. For example, the blowing agent is water. As for other additives such as foam stabilizers, any one used in the manufacture of general polyurethane foams may be used.

[0053] The density of sound-absorbing urethane foam is, for example, 70 kg / m 3 ~120kg / m 3 and preferably within 80 kg / m 3 ~100kg / m 3 If the density is within this range, even a urethane foam having a portion with a thickness of 15 mm or less can exhibit practical shock absorbing performance.

[0054] The compression strength of the sound-absorbing urethane foam is, for example, within the range of 0.05 MPa to 0.5 MPa.

[0055] An example of a sound-absorbing urethane foam according to an embodiment will be described with reference to FIGS. 1 to 3. FIG.

[0056] Fig. 1 is a plan view showing an example of a sound-absorbing urethane foam. Fig. 1 shows an example in which the sound-absorbing urethane foam is a lower limb impact absorbing material (foot panel). Fig. 2 is a cross-sectional view showing an outline of the cross section of the sound-absorbing urethane foam shown in Fig. 1 taken along line II-II. Fig. 3 is a cross-sectional view showing an outline of the cross section of the sound-absorbing urethane foam shown in Fig. 1 taken along line III-III.

[0057] The lower leg impact absorbing material 10 comprises a first portion 1, a second portion 2, and a thick portion 3. The first portion 1, the second portion 2, and the thick portion 3 are integrally molded by molding using a single metal mold to form the lower leg impact absorbing material 10. The lower leg impact absorbing material 10 can be mounted, for example, on the floor of an automobile. For example, a floor mat is laid on the lower leg impact absorbing material 10 mounted on the floor of the automobile, and both feet of the occupant are placed on the lower leg impact absorbing material via the floor mat.

[0058] The first portion 1 and the second portion 2 are thinner than the thick portion 3. The second portion 2 is generally rectangular and has end faces defined by a boundary portion 4. The first portion 1 and the thick portion 3 extend from the end faces of the second portion 2. The lower limbs impact absorbing material 10 is curved so that the boundary portion 4 between the second portion 2 and the first portion 1 and the thick portion 3 forms a valley. The boundary portion 4 forms a valley on one side of the lower limbs impact absorbing material 10, but forms a peak on the other side.

[0059] The lower limb impact absorbing material 10 has a surface 5 where the second portion 2, the first portion 1, and the thick portion 3 form a valley. The lower limb impact absorbing material 10 has a back surface 6 where the second portion 2, the first portion 1, and the thick portion 3 form a mountain. The thick portion 3 has a convex shape on the surface 5. In other words, the thick portion 3 has a structure on the surface 5 that protrudes beyond the surface of the first portion 1, with the surface of the first portion 1 being used as a reference.

[0060] When the lower leg impact absorbing material 10 is mounted on the floor of an automobile, for example, the right foot of an occupant is placed on the surface 5 of the first portion 1 and the second portion 2, and the left foot of the occupant is placed on the surface 5 of the second portion 2 and the thick portion 3.

[0061] The thickness of the first portion 1 and the second portion 2 is, for example, 30 mm or less. The first portion 1 and the second portion 2 may each have a portion having a thickness of 15 mm or less. The thickness of the portion may be 10 mm or less. The thickness of the thick portion 3 is, for example, 70 mm to 110 mm.

[0062] 1 to 3, the sound-absorbing urethane foam is described as an example of a lower limb impact absorbing material, but the use of the sound-absorbing urethane foam is not particularly limited, and it is preferably used in applications requiring sound absorption and impact absorption performance. The sound-absorbing urethane foam can be used, for example, as a door interior cushioning material, a head protection material, a floor raising material, a tool box, a luggage box, a ceiling material, a seat core material, a sun visor core material, a pillar core material, etc. It is also possible to obtain a sound-absorbing urethane foam of a desired shape by cutting the foam.

[0063] [Example] Examples will be described below, but the embodiments are not limited to the examples described below.

[0064] According to the compounding recipes shown in Table 1 below, sound-absorbing urethane foams according to Examples 1 to 17, 6A, and 7A were produced by molding. The raw materials listed in Table 1 are as follows. In Table 1, the compounding ratio of each raw material is shown in parts by weight. However, "index" indicates the isocyanate group equivalent (concentration) in the polyisocyanate relative to the total of the active hydroxyl group equivalent (concentration) in the polyol, the hydroxyl group equivalent (concentration) of other materials containing an active hydroxyl group equivalent (concentration), and the hydroxyl group equivalent (concentration) of water.

[0065] Further, sound-absorbing urethane foams according to Examples 18 to 23 were produced by molding according to the compounding recipes shown in Table 2 below. The raw materials shown in Table 2 are as follows. In Table 2, the compounding ratio of each raw material is shown in parts by weight.

[0066] (1) Polyol 1: trade name: QB8000 (weight average molecular weight 8000, polyoxyethylene content 80%) manufactured by Toho Chemical Industry Co., Ltd. (2) Polyol 2; trade name: EP-901P (weight average molecular weight: 7000, polyoxyethylene content: 15%) manufactured by Mitsui Chemicals SKC Polyurethanes Co., Ltd. (3) Polyol 3; Trade name of Dow Chemical: NC630 (weight average molecular weight 7400, polyoxyethylene content 14% to 16%) (4) Polyol 4; trade name: KC745 (weight average molecular weight: 5000, polyoxyethylene content: 20% to 25%) manufactured by Sanyo Chemical Industries, Ltd. (5) Polyol 5; trade name: EP330N (weight average molecular weight: 5000, polyoxyethylene content: 10% to 12%) manufactured by Mitsui Chemicals SKC Polyurethanes Co., Ltd. (6) Polyol 6; trade name: T-5000D (weight average molecular weight 5000, polyoxyethylene content 0%) manufactured by Mitsui Chemicals SKC Polyurethanes Co., Ltd. (7) Polyol 7; Trade name of Dow Chemical: CP1421 (weight average molecular weight 5000, polyoxyethylene content 75%) (8) Polyol 8; Trade name: V4053 (weight average molecular weight 12,500, polyoxyethylene content 69%) manufactured by Dow Chemical (9) Polyol 9; trade name of Mitsui Chemicals SKC Polyurethanes Co., Ltd.: T-3000S (weight average molecular weight 3000, polyoxyethylene content 0%) (10) Additive A: Trade name: EM ALEX DEG-di-O (diethyl glycol dioleate) manufactured by Nippon Nyukazai Co., Ltd. (11) Additive B: Trade name: SF2962 manufactured by Dow Corning Toray Co., Ltd. (12) Additive C: Trade name of Toray Dow Corning Co., Ltd.: VORASURF 1280 additive (13) Antioxidant: Trade name: Irganox 1135 manufactured by BASF Japan Ltd. (14) Catalyst A: N-(dimethylpropyl)diisopropylamine (DPA: N-N, N'-diisopropanolamine) (resinification catalyst) (15) Catalyst B: Trade name: TMR7 (trimerization catalyst) manufactured by Air Products Japan Co., Ltd. (16) Catalyst C: Diethanolamine (DEA) (surface modification catalyst) (17) Catalyst D: Trade name: Niax catalyst A-1 (foam catalyst) manufactured by Momentive Performance Materials, Inc. (18) Foaming agent: Water (19) Polyisocyanate: Trade name: Sumidur 44 V 20 L, manufactured by Sumika Covestro Urethane Co., Ltd.

[0067] [Table 1]

[0068] [Table 2]

[0069] (Example 1) According to the formulation shown in Table 1 (by hand foaming), raw materials other than polyisocyanate, i.e., polyol component, additives, antioxidant, catalyst and foaming agent were blended to prepare a polyol-containing mixture in a disposable cup. The polyol component according to Example 1 includes polyol 1, polyol 2 and polyol 9. The obtained polyol-containing mixture is called liquid A. The temperature of liquid A was adjusted to 37°C ± 2°C. In addition, polyisocyanate was prepared as liquid B, and the temperature of liquid B was adjusted to 37°C ± 2°C.

[0070] A mold for making samples with inner dimensions of 350 mm width, 350 mm depth, and 10 mm height was prepared, and the mold was heated to a temperature range of 65°C to 70°C and the temperature was maintained. The temperature was measured with a surface thermometer. The mold consisted of a cylindrical lower mold with a bottom, only the top surface of which was open, and an upper mold whose top surface could be closed.

[0071] Next, the liquid B was added to the liquid A prepared in the disposable cup, and the mixture was stirred and mixed for 5 seconds to obtain a mixed solution. Here, when the total weight parts of the polyol components were 100, the weight parts of the liquid A containing the polyol components were 160.4 parts by weight, and the weight parts of the liquid B were 235.5 parts by weight. The obtained mixed solution was immediately poured into the lower mold of the mold, and the upper surface of the lower mold was closed using the upper mold, and cured for 6 minutes. During this time, the surface temperature of the mold was maintained at 65°C to 70°C. After that, the mold was removed from the mold and left to stand at room temperature for 2 days to obtain a sound-absorbing urethane foam having dimensions of 350mm x 350mm x 10mm.

[0072] (Example 2) A sound-absorbing urethane foam was obtained in the same manner as in Example 1, except that the amount of polyisocyanate in the compounding recipe was changed to 376.8 parts by weight, thereby changing the index to 160.

[0073] (Example 3) A sound-absorbing urethane foam was obtained in the same manner as in Example 1, except that the amount of catalyst C (DEA) was 1.24 parts by weight.

[0074] (Example 4) A sound-absorbing urethane foam was obtained in the same manner as in Example 3, except that the amount of polyisocyanate in the compounding recipe was changed to 288.3 parts by weight, thereby changing the index to 120.

[0075] (Example 5) A sound-absorbing urethane foam was obtained in the same manner as in Example 3, except that the amount of polyisocyanate in the compounding recipe was changed to 336.4 parts by weight, thereby changing the index to 140.

[0076] (Example 6) A sound-absorbing urethane foam was obtained in the same manner as in Example 3, except that the amount of polyisocyanate in the compounding recipe was changed to 384.4 parts by weight, thereby changing the index to 160.

[0077] (Example 7) A sound-absorbing urethane foam was obtained in the same manner as in Example 3, except that the amount of polyisocyanate in the compounding recipe was changed to 600.7 parts by weight, thereby changing the index to 250.

[0078] (Example 8) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 3 was used instead of Polyol 2.

[0079] (Example 9) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 4 was used instead of Polyol 2.

[0080] (Example 10) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 5 was used instead of Polyol 2.

[0081] (Example 11) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 6 was used instead of Polyol 2.

[0082] (Example 12) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 7 was used instead of Polyol 2.

[0083] (Example 13) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that Polyol 8 was used instead of Polyol 2.

[0084] (Example 14) A sound-absorbing urethane foam was obtained in the same manner as in Example 1, except that the amount of catalyst C (DEA) was 2.48 parts by weight.

[0085] (Example 15) A sound-absorbing urethane foam was obtained in the same manner as in Example 14, except that the amount of polyisocyanate in the formulation was changed to 392.0 parts by weight, thereby changing the index to 160.

[0086] (Example 16) A sound-absorbing urethane foam was obtained in the same manner as in Example 1, except that the compounding ratio of each raw material was changed as shown in the column for Example 16 in Table 1.

[0087] (Example 17) A sound-absorbing urethane foam was obtained in the same manner as in Example 16, except that the amount of polyisocyanate in the compounding recipe was changed to 605.1 parts by weight, thereby changing the index to 250.

[0088] (Example 6A) A sound-absorbing urethane foam was obtained in the same manner as in Example 6, except that a sample preparation mold with inner dimensions of 350 mm width, 350 mm depth, and 30 mm height was used.

[0089] (Example 7A) A sound-absorbing urethane foam was obtained in the same manner as in Example 6A, except that the amount of polyisocyanate in the compounding recipe was changed to 576.6 parts by weight, thereby changing the index to 240.

[0090] (Example 18 to Example 23) A sound-absorbing urethane foam was obtained in the same manner as in Example 1, except that the compounding ratio of each raw material was changed as shown in Table 2.

[0091] <Moldability evaluation> The moldability (curability) of each of the sound-absorbing urethane foams obtained in Examples 1 to 23 and Examples 6A and 7A was evaluated by sensory evaluation. The urethane foam in a good condition when demolded was rated as "○", the foam in which finger marks remained when demolded by hand (insufficient curing) or the design surface peeled off was rated as "△", and the urethane foam collapsed or was in a severely insufficient curing state was rated as "×". Among Examples 1 to 23, Examples 6, 8-10, 12, 13, 15, and 18 to 23, which had a cure property of "○", had design surfaces on both sides of the 10 mm thick block. Examples of the evaluation "×" include, for example, that the foam was stringy when demolded, that the foam was ragged and brittle, or that the cells inside the foam collapsed and collapsed. In addition, if the design surface peels off when demolded, the sound absorbing performance and air permeability will change, so when multiple urethane foams are produced in continuous operation, it tends to be difficult to obtain urethane foams with stable sound absorbing performance. Therefore, it is preferable that the design surface is cured so that it does not peel off when demolded.

[0092] <Sound absorption performance evaluation> According to the method for measuring the normal incidence sound absorption coefficient described in the embodiment, the sound absorbing urethane foam according to each example was evaluated for sound absorption performance. In the entire frequency range of 1000Hz to 3150Hz, those having a normal incidence sound absorption coefficient of 40% or more were evaluated as "○", and those having a band in which the normal incidence sound absorption coefficient is less than 40% in the frequency range of 1000Hz to 3150Hz were evaluated as "×". However, for those evaluated as "×" in the above moldability evaluation, no evaluation was performed because the sound absorption performance could not be appropriately evaluated. In Table 1, examples that were not evaluated are indicated by diagonal lines in the "sound absorption performance" row.

[0093] As shown in Tables 1 and 2, the sound-absorbing urethane foams according to Examples 5-13, 15-16, 18-23, 6A and 7A had practical moldability. In other words, the moldability of these examples was evaluated as "good" or "good." Therefore, it was possible to evaluate the sound-absorbing performance.

[0094] Furthermore, as shown in Table 1, for Examples 6A and 7A, the thickness of the urethane foam to be evaluated is 30 mm.

[0095] Sound absorption coefficient graphs for Examples 5-13, 15-16, 18-23, 6A, and 7A, for which sound absorption coefficient measurements were possible, are shown in Figures 6-10. Figure 6 shows the results of Examples 6, 8-10. Figure 7 shows the results of Examples 6, 11-13, and 16. Figure 8 shows the results of Examples 5-7 and 15. Figure 9 shows the results of Examples 6A and 7A. Figure 10 shows the results of Examples 18-23. In each sound absorption coefficient graph, the horizontal axis shows frequency (Hz) and the vertical axis shows sound absorption coefficient (%).

[0096] <Density measurement> The density of the sound-absorbing urethane foam in each example was measured and found to be 90 kg / m 3 It was.

[0097] The density was evaluated in accordance with the measurement method specified in JIS K 7222:2005.

[0098] FIG. 6 shows the sound absorption coefficient measurement results of sound-absorbing urethane foams according to Examples 6 and 8-10, which have a common index of 160. These examples are examples in which the polyol corresponding to the above-mentioned polyol B was changed. The sound-absorbing urethane foams according to Examples 6 and 8-10 contained polyol 2 (EP-901P), polyol 3 (NC630), polyol 4 (KC745), and polyol 5 (EP330N) as the polyol component. All of these polyols had a weight average molecular weight in the range of 4000 to 12000 and an ethylene oxide content in the range of 5% by weight or more and less than 50% by weight, so the obtained sound-absorbing urethane foams had a normal incidence sound absorption coefficient of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz.

[0099] FIG. 7 also shows the sound absorption coefficient measurement results of the sound-absorbing urethane foams of Examples 6, 11-13, and 16, which have a common index of 160. Unlike Examples 6 and 8-10, the sound-absorbing urethane foams of Examples 11-13 did not contain a polyol component corresponding to polyol B. Instead, they contained a polyol component with an ethylene oxide content of 50% by weight or more. Therefore, the air permeability of the obtained sound-absorbing urethane foam is increased, the conversion of incident waves to thermal energy inside the urethane is reduced, and the incident waves are difficult to absorb. Therefore, it is considered that the sound absorption coefficient in the range of 1000 Hz to 3150 Hz for Examples 11-13 was inferior to that of Example 6. In addition, the sound-absorbing urethane foam of Example 16 contained only polyol 1 (QB8000) and polyol 9, which have a weight average molecular weight of 4000 or more and an ethylene oxide content of 80%, as polyol components, and therefore had many open cells, and therefore may not have been excellent in sound absorption performance in the low frequency range.

[0100] FIG. 8 shows the sound absorption coefficient measurement results of the sound-absorbing urethane foams of Examples 5-7 and 15. Examples 5-7 and 15 are examples of sound-absorbing urethane foams manufactured with the same recipe except for the content of catalyst C (DEA) and the index conditions. All of these examples had a normal incidence sound absorption coefficient of 40% or more over the entire frequency range of 1000Hz to 3150Hz. Example 7, which has an index of 250, had a poor sound absorption coefficient at 1000Hz compared to Examples 5, 6, and 15. On the other hand, Example 7 had the best sound absorption coefficient at 3150Hz among these examples. From this, it can be seen that by increasing the index, the frequency band in which sound can be efficiently absorbed tends to change from a low frequency band to a high frequency band of about 2000Hz to 6000Hz.

[0101] The prescription of Example 6A is the same as that of Example 6. The prescription of Example 7A is almost the same as that of Example 7, except that the index is 240. As is clear from FIG. 9, when the thickness of the block is 30 mm when the sound absorption coefficient is measured, the sound absorption coefficient at frequencies below 2000 Hz is significantly improved. On the other hand, it can be seen that there is a problem in that the sound absorption coefficient in the low frequency band is significantly reduced when the thickness of the block is 10 mm. The sound-absorbing urethane foam according to the embodiment has excellent sound absorption performance because the normal incident sound absorption coefficient is 40% or more in the entire frequency range of 1000 Hz to 3150 Hz even when the thickness of the block is 10 mm.

[0102] In Examples 1 to 15 and Examples 6A and 7A shown in Table 1, the content ratio of polyol 1 corresponding to polyol A in the polyol component was 57.85% by weight. In contrast, in Examples 18 to 23 shown in Table 2, the content ratio of polyol 1 corresponding to polyol A in the polyol component was 70% by weight to 75% by weight. Even when the content ratio of polyol A in the polyol component was increased in this way, the moldability of the obtained sound-absorbing urethane foam was excellent, and the normal incidence sound absorption coefficient was 40% or more in the entire frequency range of 1000 Hz to 3150 Hz. For example, when the weight ratio of polyol A in the weight of the polyol component is within the range of 35% by weight to 80% by weight, a sound-absorbing urethane foam with excellent sound-absorbing performance can be obtained.

[0103] In Examples 1 to 15 and Examples 6A and 7A shown in Table 1, the content ratio of polyols 2 to 8 corresponding to polyol B in the polyol component was 24.79% by weight. In contrast, in Examples 18 to 23 shown in Table 2, the content ratio of polyol 2 corresponding to polyol B in the polyol component was 5% by weight to 10% by weight. Even when the content ratio of polyol B in the polyol component was reduced in this way, the moldability of the obtained sound-absorbing urethane foam was excellent, and the normal incidence sound absorption coefficient was 40% or more in the entire frequency range of 1000 Hz to 3150 Hz. For example, when the weight ratio of polyol B in the weight of the polyol component is within the range of 5% by weight to 40% by weight, a sound-absorbing urethane foam with excellent sound-absorbing performance can be obtained.

[0104] Figure 10 shows the sound absorption coefficient measurement results for the sound-absorbing urethane foams of Examples 18 to 23. As shown in the graph in Figure 10, the sound-absorbing urethane foams of Examples 18 to 23 all had a normal incidence sound absorption coefficient of 40% or more over the entire frequency range of 1000 Hz to 3150 Hz.

[0105] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]

[0106] 1...first part, 2...second part, 3...thick part, 4...boundary part, 5...surface, 6...back side, 10...lower limb shock absorbing material, 100...porous elastic body, 101...skeleton, 102...void, 103...air-propagating wave, 104...solid-propagating wave, SW...sound wave, I...incident wave, R...reflected wave, T...transmitted wave, r...thermal energy.

Claims

1. A sound-absorbing urethane foam obtained by foaming in a reaction system containing a polyol, a polyisocyanate, a blowing agent, a catalyst, and an additive, The polyol includes polyol A having a weight average molecular weight in the range of 2,000 to 12,000 and an ethylene oxide content of 50% by weight or more, and polyol B having a weight average molecular weight in the range of 4,000 to 12,000 and an ethylene oxide content in the range of 5% by weight or more and less than 50% by weight, the weight ratio of the polyol A to the weight of the polyol is within a range of 35% by weight to 80% by weight, the catalyst comprises diethanolamine; The isocyanate index is in the range of 130 to 250, and A sound-absorbing urethane foam having a diameter of 29 mm and a thickness of 10 mm, in which the normal incidence sound absorption coefficient is 40% or more over the entire frequency range of 1000 Hz to 3150 Hz.

2. The thickness of the portion is 15 mm or less, 2. The sound-absorbing urethane foam according to claim 1, wherein the normal incidence sound absorption coefficient at said portion when the diameter is 29 mm and the thickness is 10 mm is 40% or more over the entire frequency range of 1000 Hz to 3150 Hz.

3. 3. The sound-absorbing urethane foam according to claim 1, wherein the weight ratio of said polyol B to the weight of said polyol is within a range of 5% to 40%.

Citation Information

Patent Citations

  • Open-cell rigid polyurethane foam, method for producing the same and sound absorbing material

    JP2005060414A

  • Rigid polyurethane foam

    JP2005272806A

  • Vibration deadening sound absorption material and metho for producing the same

    JP2008274092A

  • Sound absorption shock absorbing material, and method of manufacturing the same

    JP2013047338A

  • Two liquid reaction type urethane resin composition and method for manufacturing the same

    JP2019178207A